2014
DOI: 10.1016/j.exger.2013.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional survival-signaling and stress-intolerance in aged murine and human myocardium

Abstract: Changes in cytoprotective signaling may influence cardiac aging, and underpin sensitization to ischemic insult and desensitization to ‘anti-ischemic’ therapies. We tested whether age-dependent shifts in ischemia-reperfusion (I-R) tolerance in murine and human myocardium are associated with reduced efficacies and coupling of membrane, cytoplasmic and mitochondrial survival-signaling. Hormesis (exemplified in ischemic preconditioning; IPC) and expression of proteins influencing signaling/stress-resistance were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
65
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(76 citation statements)
references
References 68 publications
11
65
0
Order By: Relevance
“…In adult rats, µ-OR are absent. Most of the studies were performed on young animals, whereas intrinsic protective tolerance against I/R injury may fail with age in humans [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…In adult rats, µ-OR are absent. Most of the studies were performed on young animals, whereas intrinsic protective tolerance against I/R injury may fail with age in humans [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Myocardial ischemia-reperfusion tolerance declines with age in association with dysfunctional homeostasis and transduction of survival signals. Differential changes in proteins governing caveolae such as reduced Cav-3, cholesterol, and caveolae may contribute to signal dysfunction and stress-intolerance (133).…”
Section: Caveolin-3 and Cardiac Pathologymentioning
confidence: 99%
“…In fact, the age-dependent impairment involves a wide signal transduction changes from the myocardial cell membrane receptors to mitochondrial targets (14), which was illustrated in a systematic and rigorous study by Peart et al Similarly, Zhu et al (31) demonstrated that the phosphorylation levels of Akt and GSK3β were remarkably elevated in the aged rats and isoflurane failed to perform cardioprotection related to incapable of further increasing the survival protein phosphorylation to reduce mPTP opening following IRI. In addition, they tried to use SB-216763 and cyclosporine A (CsA), GSK3β and mPTP inhibitor respectively, but it was a pity that both SB-216763 and CsA failed to reduce myocardial infarct size in the aged rats (32,33).…”
Section: Agingmentioning
confidence: 99%
“…Numerous studies indicate that age-related intolerance to IRI is associated with alterations of membrane-sensitive cytoprotective signaling and cardiac mitochondrial function (14,24). Especially, RISK-GSK3β pathway altered in aged hearts will undertake the responsibility for the suppression of conditioning protection (Table 1) .…”
Section: Agingmentioning
confidence: 99%
See 1 more Smart Citation